2018
DOI: 10.1200/jco.2018.78.2128
|View full text |Cite
|
Sign up to set email alerts
|

Communication About Prognosis With Adolescent and Young Adult Patients With Cancer: Information Needs, Prognostic Awareness, and Outcomes of Disclosure

Abstract: Purpose Communication about prognosis affects decisions patients and family members make about cancer care, and most patients say they want to know about their chances of cure. We sought to evaluate experiences with prognosis communication among adolescents and young adults (AYAs) with cancer. Patients and Methods We surveyed 203 AYAs with cancer age 15 to 29 years (response rate, 74%) treated at Dana-Farber Cancer Institute and their oncologists. Patients were approached within 6 weeks of diagnosis and asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(112 citation statements)
references
References 44 publications
5
105
0
2
Order By: Relevance
“…Cancer patients aged 15–29 at diagnosis, seen at Dana‐Farber Cancer Institute (DFCI), Boston, Massachusetts, were surveyed from April 2014 to October 2017. Methods have been previously described . To be eligible, patients had to be literate in English and 1–6 weeks from diagnosis at first contact.…”
Section: Methodsmentioning
confidence: 99%
“…Cancer patients aged 15–29 at diagnosis, seen at Dana‐Farber Cancer Institute (DFCI), Boston, Massachusetts, were surveyed from April 2014 to October 2017. Methods have been previously described . To be eligible, patients had to be literate in English and 1–6 weeks from diagnosis at first contact.…”
Section: Methodsmentioning
confidence: 99%
“…Several recent studies focusing on AYA cancer patients’ involvement in EOL discussions and decision‐making have found that most AYA patients desire to participate in EOL decision‐making and wish to be communicated with honestly . For example, one study found that 83% of AYA patients considered prognostic information to be extremely or very important . Additionally, a study of adolescents nearing EOL found that they comprehended the context and ramifications of their decisions .…”
Section: End Of Lifementioning
confidence: 99%
“…Parents of children with cancer rate the communication skills of their child's oncologist as a critical component of the illness and treatment experience, and parents are more likely to believe that oncologists provided high quality information when they also rate the provider's communication style highly . Better communication has also been associated with parental report of increased hope, decreased decisional regret, and improved psychosocial outcomes …”
Section: Introductionmentioning
confidence: 99%